2005
DOI: 10.1038/emm.2005.19
|View full text |Cite
|
Sign up to set email alerts
|

HCV core protein promotes liver fibrogenesis via up-regulation of CTGF with TGF-β1

Abstract: Liver cirrhosis is one of the major complications of hepatitis C virus (HCV) infection, but the mechanisms underlying HCV-related fibrogenesis are still not clear. Although the roles of HCV core protein remain poorly understood, it is supposed to play an important role in the regulation of cellular growth and hepatocarcinogenesis. The aim of this study was to examine the role of HCV core protein on the hepatic fibrogenesis. We established an in vitro co-culture system with primary hepatic stellate cell (HSC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 38 publications
6
75
0
Order By: Relevance
“…Moreover, expression of HCV nonstructural and core proteins induces stellate cell proliferation, release of inflammatory signals, 202 and CTGF, 203 although interaction of HCV E2 protein stimulates MMP-2 expression. 204 Furthermore, hepatocytes harboring replicating HCV in culture produce fibrogenic stimuli towards stellate cells.…”
Section: Hcv and Hivmentioning
confidence: 99%
“…Moreover, expression of HCV nonstructural and core proteins induces stellate cell proliferation, release of inflammatory signals, 202 and CTGF, 203 although interaction of HCV E2 protein stimulates MMP-2 expression. 204 Furthermore, hepatocytes harboring replicating HCV in culture produce fibrogenic stimuli towards stellate cells.…”
Section: Hcv and Hivmentioning
confidence: 99%
“…However, in other diseases, including arthritis (Manns et al 2006;Tanaka et al 2005) and viral hepatitis (Fukutomi et al 2005;Shin et al 2005), CCN2 and CCN5 are similarly expressed. CCN2 and CCN5 have opposite expression patterns in vascular SMC.…”
Section: Introductionmentioning
confidence: 99%
“…The HCV Core transgenic mice suggested that core protein may play an important role in HCVinduced steatosis and HCC (Moriya et al, 1997;Moriya et al, 1998;Shin et al, 2005). Recently, Lerat et al suggested that the expression of the structural proteins enhances a low background of steatosis in C57BL/6 mice, while the additional low-level expression of the nonstructural proteins increases the risk of cancer (Lerat et al, 2002).…”
Section: Discussionmentioning
confidence: 99%